Passive immunization with an extended half-life monoclonal antibody protects Rhesus macaques against aerosolized ricin toxin - Roy, Chad J. (NPJ Vaccines, 2020)
Inhalation of ricin toxin (RT), a Category B biothreat agent, provokes an acute respiratory distress syndrome marked by pro-inflammatory cytokine and chemokine production, neutrophilic exudate, and pulmonary edema. The severity of RT exposure is attributed to the tropism of the toxin’s B subunit (RTB) for alveolar macrophages and airway epithelial cells, coupled with the extraordinarily potent ribosome-inactivating properties of the toxin’s enzymatic subunit (RTA). While there are currently no vaccines or treatments approved to prevent RT intoxication, we recently described a humanized anti-RTA IgG(1) MAb, huPB10, that was able to rescue non-human primates (NHPs) from lethal dose RT aerosol challenge if administered by intravenous (IV) infusion within hours of toxin exposure. We have now engineered an extended serum half-life variant of that MAb, huPB10-LS, and evaluated it as a pre-exposure prophylactic. Five Rhesus macaques that received a single intravenous infusion (25 mg/kg) of huPB10-LS survived a lethal dose aerosol RT challenge 28 days later, whereas three control animals succumbed to RT intoxication within 48 h. The huPB10-LS treated animals remained clinically normal in the hours and days following toxin insult, suggesting that pre-existing antibody levels were sufficient to neutralize RT locally. Moreover, pro-inflammatory markers in sera and BAL fluids collected 24 h following RT challenge were significantly dampened in huPB10-LS treated animals, as compared to controls. Finally, we found that all five surviving animals, within days after RT exposure, had anti-RT serum IgG titers against epitopes other than huPB10-LS, indicative of active immunization by residual RT and/or RT-immune complexes.